Extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue of the dura mimicking meningioma: a case report and literature review - Glinka, Piotr; Sobstyl, Michał; Rymkiewicz, Grzegorz; Wierzba-Bobrowicz, Teresa; Paszkiewicz-Kozik, Ewa; Grajkowska, Wiesława (Folia Neuropathologica, 2024)
MALT lymphoma of the dura is a very rare type of low-grade B-cell lymphoma. Little more than 100 cases have been reported in the literature to date. We report a 43-year-old woman who was referred to hospital because of a series of three tonic-clonic seizures on the day of admission. Neurological examination revealed confusion and aphasia. Magnetic resonance imaging (MRI) showed a contrast-enhanced, broad-based lesion along the dura in the left parieto-occipital area. The suspicion of an en plaque meningioma was raised. The tumour invaded the brain parenchyma with visible extension into the brain sulci. There was a marked brain oedema surrounding the lesion and causing the midline shift 8 mm to the right. After stabilization of neurological condition (intravenous diuretics and steroids), the operation was performed. The diagnosis of dural MALT lymphoma was established. During the pathological examination, it was especially problematic to distinguish MALT lymphoma from follicular lymphoma, but the final diagnosis was MALT lymphoma. Surgical partial removal with additional R-CVP immunochemotherapy (rituximab, cyclophosphamide, vincristine and prednisone) resulted in complete remission. The follow-up period is 1 year. Our presented case of a MALT lymphoma highlights the fact that surgical partial removal with additional immunochemotherapy is an available option in these rare intracranial tumours.